Development of European Rail Transport in the Context of a Global Health Crisis and Geopolitical Instability - Dimitrov, Georgi (Research Papers, 2025)
Railway transport plays an extremely important role in the transport systems of European countries, carrying out land transport of passengers and goods over short, medium and long distances. This article analyzes the development of freight and passenger rail transport in a significant part of European countries. Trends in the quantities of goods transported and the freight transport activity performed by European railway transport are observed in relation to the level of the gross domestic product of the respective countries. In the case of passenger rail transport, the number of passengers transported and the work performed in relation to the population of individual countries are analyzed. The analyzed period covers the time before and after the onset of the global health crisis caused by COVID-19, as well as the start (for the first time since World War II) of military operations on the territory of Europe. The main objective of the study is to track trends in the demand for freight and passenger rail transport on the territory of Europe and to take into account the impact of the crisis caused by the pandemic and geopolitical instability on the railway transport of individual European countries.